An Inverse Model for Estimating the Optical Absorption and Backscattering Coefficients of Seawater From Remote‐Sensing Reflectance Over a Broad Range of Oceanic and Coastal Marine Environments. Issue 3 (25th March 2018) - Loisel, Hubert; Stramski, Dariusz; Dessailly, David; Jamet, Cédric; Li, Linhai; Reynolds, Rick A.
Abstract: We present an inverse model (referred to as LS2) for estimating the inherent optical properties (IOPs) of seawater, specifically the spectral absorption, a ( λ ), and backscattering, b b ( λ ), coefficients within the ocean surface layer, from measurements of ocean remote‐sensing reflectance, R rs ( λ ). The nonwater absorption, a nw ( λ ), and particulate backscattering, b bp ( λ ), coefficients can be derived after subtracting pure seawater contributions. The LS2 requires no spectral assumptions about IOPs and provides solutions at arbitrary light wavelengths in the visible spectrum independently of one another. As the LS2 can operate with the inputs of R rs ( λ ) and solar zenith angle it is applicable to satellite ocean color remote sensing. The model can also operate with additional input of the diffuse attenuation coefficient of downward irradiance, which provides somewhat improved model performance for applications using in situ radiometric measurements as inputs. The evaluation of LS2 with a synthetic data set that is free of measurement errors indicates good performance for IOPs in the visible spectrum, except for a nw ( λ ) in the long‐wavelength portion of the spectrum where a nw ( λ ) contributes only a few percent to a ( λ ) under typical open ocean conditions. The good performance is characterized by a median absolute percent difference between the model‐derived and true values of IOPs, which is generally <20%, and the median ratio of model‐derived to true values <10%. The satisfactory model performance is also demonstrated through validation analysis based on extensive data sets comprising coincident in situ measurements of R rs ( λ ) and IOPs as well as a match‐up data set comprising satellite‐derived R rs ( λ ) and in situ IOP measurements. Key Points: An improved inverse reflectance model for estimating ocean inherent optical properties (IOPs) with no spectral assumptions was developed Model evaluation with a synthetic data set indicates that algorithmic formulations are adequate, which results in good IOP retrievals Satisfactory model performance is validated with extensive data sets of in situ measurements and a satellite‐in situ match‐up data set